2019
DOI: 10.24321/2455.7048.201816
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Preventive Practices about Occupational Health Hazard among Safai Karmchari of Municipality in Delhi

Abstract: Background: Safai karmchari plays an important role in maintaining the health and hygiene in the cities. This job exposes safai karmchari to a variety of risk factors such as dust, volatile organic matter and mechanical stress, which makes them susceptible to certain occupational diseases. The aim of this study was to find out the awareness about occupational health hazard and safety measures practiced by safai karmchari. Materials and Methods: This descriptive study had been carried out during the month of De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…33 There were studies promoting health in this group which were found to be effective in improving knowledge on anemia prevention and reproductive health, 46 and knowledge on the occupational hazard and hygiene. 52 Another recent study in Puducherry reported that 44.8%, 19%, and 10% were using footwear, gloves, and facemask respectively and none were using goggles or suits. 44 It could be observed from these studies that the use of gloves is comparatively less than other forms of PPE being used.…”
Section: Documented Various Types Of Dermatologicalmentioning
confidence: 98%
“…33 There were studies promoting health in this group which were found to be effective in improving knowledge on anemia prevention and reproductive health, 46 and knowledge on the occupational hazard and hygiene. 52 Another recent study in Puducherry reported that 44.8%, 19%, and 10% were using footwear, gloves, and facemask respectively and none were using goggles or suits. 44 It could be observed from these studies that the use of gloves is comparatively less than other forms of PPE being used.…”
Section: Documented Various Types Of Dermatologicalmentioning
confidence: 98%